2012
DOI: 10.13005/bbra/1017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of bacteriocinogenic Lactobacillus species isolated from fermented Uttapam batter

Abstract: Lactic acid bacteria (LAB) are protective and generally recognized as safe (GRAS) organisms. The antimicrobial compounds produced by LAB act effectively against several pathogenic organisms, hence they are well-employed as food preservative. This study aims at isolation and characterization of potent bacteriocinogenic lactobacilli from fermented Uttapam batter. Eighteen bacilli showing wide spectrum of inhibitory property against Gram positive and negative organisms were grouped using RAPD, physiological and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…Earlier study showed that the eight isolates were bacteriocinogenic in nature as there was loss of activity after protease treatment (Saraniya and Jeevaratnam 2012).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Earlier study showed that the eight isolates were bacteriocinogenic in nature as there was loss of activity after protease treatment (Saraniya and Jeevaratnam 2012).…”
Section: Resultsmentioning
confidence: 95%
“…Antibacterial activity assay using cell-free supernatant concentrate (CFSC) adjusted to pH 6.0 was carried out against intestinal pathogens (Table 1) by agar well diffusion assay (Saraniya and Jeevaratnam 2012). The pathogens used were obtained from the Microbial Type Culture Collection (MTCC), at Institute of Microbial Technology, Chandigarh, India, and maintained in MRS broth for LAB isolates and soya bean casein digest broth for non-LAB organisms and stored at −20°C with 30 % glycerol.…”
Section: Strains and Antibacterial Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar utilization profile of isolates was resolved by using the HiCarbo Kit (Himedia, India). The configurations of lactic acid enantiomers and their concentrations were determined by enzymatic method as described earlier [16] …”
Section: Classical Characterization Of Potent Antifungal and Antibactmentioning
confidence: 99%
“…In addition, several low molecular weight compounds like benzoic acid, lactic acid, phenyl lactic acid, methylhydantoine, mevalonolactone produced by LAB also exhibits antifungal and antimicrobial properties. Earlier, we have identified many bacteriocinogenic lactobacilli isolates from fermented Uttapam batter (a cereal based fermented food source) to subspecies level showing broad spectrum of antibacterial activity (Saraniya and Jeevaratnam, 2012). Among the isolates, Lactobacillus pentosus SJ65 was found to be most potent and taken up for further study.…”
Section: Introductionmentioning
confidence: 99%